Determinants of psychiatric disorders in children refugees in Turkey's Yazidi refugee camp - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2018)
Objective: To examine the mental health states of a sample of Yazidi refugee children and adolescents who migrated from war-torn Iraq's Sinjar region and to determine the risk and protective factors for psychiatric disorders among the refugee children and adolescents. Method: The participants of this research were children and adolescents between ages 6 and 17 who live in a refugee camp in Turkey. Their parents/guardians provided written informed consents for the research. The research was approved by the Ethics Council of Sakarya University. Participants with intellectual disabilities and autism spectrum disorders were excluded from the study. Two child and adolescent psychiatrists speaking their native language interviewed and evaluated each of the participants. Collected data included socio-demographic information about previous and current living situations, Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime - Turkish Version (K-SADS-PL). Results: One hundred and thirty-six children and adolescents (76 boys, 63 girls; mean age=11.05 +/- 3.11(SD)). At the time of the assessment, 43.4% had posttraumatic stress disorder (PTSD) (n=59), 27.9% depression (n=38), 10.3% nocturnal enuresis (n=14), 9.6% behavioural problems (n=7), and 5.1% anxiety disorders (n=13). Conclusions: Many of the refugee children and adolescents had developed psychiatric disorders, or are at risk for PTSD and depression. Also, the ongoing ambiguity regarding their living conditions, interruption of their education, a lack of hope for the future and anxiety regarding the ones they left behind are considered to be risk factors for the development of psychiatric and social problems in the future. Living with family members and not having losses from the immediate family are protective factors.
Keywords: Posttraumatic stress disorder; depression; refugees; psychiatric disorder; risk factor; protective factor; POSTTRAUMATIC-STRESS-DISORDER; MENTAL-HEALTH; ORGANIZED VIOLENCE; COMMUNITY SAMPLE; TRAUMA; DEPRESSION; ADOLESCENT; SCHOOL; WAR; IMMIGRANT